Сучасні інформаційні методи аналізу даних - Ілляшенко, Катерина Володимирівна; Илляшенко, Екатерина Владимировна; Illiashenko, Kateryna (My University, 2015)
UK: У статті висвітлена проблематика обробки нагромадження сирої інформації на підприємствах з великими інформаційними потоками, досліджені особливості сучасних інформаційних методів аналізу даних, проаналізовані переваги методів Data Mіnіng і Knowledge Dіscovery іn Databases, визначені перспективи їх застосування на вітчизняних підприємствах. EN: In the article the range of problems of processing of accumulation of raw information on enterprises with large information flows is lightened, the features of modern informative methods of analysis of data are investigated, advantages of methods of Data Mining and Knowledge Discovery in Databases are analyzed, the prospects of their application on domestic enterprises are certain. Informatization of society has led to the fact that with the improvement of technologies for capturing and storing data collected huge amounts of diverse information. Work business involves the registration and documentation of all details of the current activity. Accumulated unstructured data form a chaotic clutter that without special treatment, have no beneficial use, moreover, complicate the process of finding the really necessary information. Modern requirements for such treatment as follows: data are unlimited and are dissimilar, the results should be concrete and understandable tools for their processing must be easy to use. One of the methods of this treatment is promising, but new to the majority of domestic enterprises data mining. Now there are two ways of obtaining information: documentary and expert. In the first case, data is loaded from multiple data sources such as documents, databases, information systems, and more. Expert method involves extracting and structuring knowledge from memory of expert as specialist of which area. A feature of the modern information processing there is a huge diverse amount of data, making untenable both statistical and expert approaches in many practical aspects, including economic. Therefore, to analyze the information stored in modern databases, methods must be efficient: easy to use, have a significant level of scalability and automaticity. This concept is the basis of modern information technologies of analysis: Data Mining and Knowledge Discovery in Databases (KDD). Global implementation of information technology requires new approaches to the analysis of activity of enterprises that need to expand its analytical activities and to more effectively use modern information methods analysis. The use of techniques such as data mining and KDD, can allow enterprises to create a new paradigm of action in relation to modern conditions. RU: В статье высветлена проблематика обработки накопления сырой информации на предприятиях с большими информационными потоками, исследованы особенности современных информационных методов анализа данных, проанализированы преимущества методов Data Mіnіng и Knowledge Discovery in Databases, определены перспективы их применения на отечественных предприятиях.
Modern information methods of data analysis
Keywords: інформація; аналіз; дані; Data Mіnіng; Knowledge Dіscovery іn Databases; information; analysis; data